2018
DOI: 10.17159/sajs.2018/20170269
|View full text |Cite
|
Sign up to set email alerts
|

I believe I can do science: Self-efficacy and science achievement of Grade 9 students in South Africa

Abstract: An important component of an individual’s scientific literacy is a positive attitude towards science. However, emphasis is too often placed on achievement scores rather than attitude. While individuals’ relative levels of problem-solving skills, inherent aptitudes for the subject matter and teaching practices are conveyed through achievement scores, attitudes to science convey individuals’ emotional evaluation of the subject. Attitudes have a strong impact on behaviour: through either facilitating the learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
(60 reference statements)
4
17
0
Order By: Relevance
“…Our results revealed that the science self-efficacy was more strongly connected to science achievement than that of interest, societal relevance of attitude toward science, and mixed attitude. This finding was in accordance with the proposition that the effect of self-efficacy on students' learning performance could be stronger than some other dimensions (e.g., value, interest; Lam and Lau, 2014 ), and self-efficacy could significantly predict science learning (e.g., Kaya and Bozdag, 2016 ; Juan et al, 2018 ; Kirbulut and Uzuntiryaki-Kondakci, 2019 ). A meta-analysis conducted by Sun et al ( 2021 ) also showed that there was a positive correlation between students' self-efficacy and writing achievement in a second language.…”
Section: Discussionsupporting
confidence: 88%
“…Our results revealed that the science self-efficacy was more strongly connected to science achievement than that of interest, societal relevance of attitude toward science, and mixed attitude. This finding was in accordance with the proposition that the effect of self-efficacy on students' learning performance could be stronger than some other dimensions (e.g., value, interest; Lam and Lau, 2014 ), and self-efficacy could significantly predict science learning (e.g., Kaya and Bozdag, 2016 ; Juan et al, 2018 ; Kirbulut and Uzuntiryaki-Kondakci, 2019 ). A meta-analysis conducted by Sun et al ( 2021 ) also showed that there was a positive correlation between students' self-efficacy and writing achievement in a second language.…”
Section: Discussionsupporting
confidence: 88%
“…Graduate self-efficacy is vital to academic and employability success since it is instrumental in overcoming obstacles, managing stressful situations, and achieving personal and professional goals. General research findings support this assumption, suggesting that the level of one’s self-efficacy has implications for changes in behaviour, stress management, and academic and career choices ( Gharetepeh et al, 2015 ; Juan et al, 2018 ). On the other hand, those who have a weaker sense of self-efficacy have low ambitions and weaker commitment to goals, retreat from difficult tasks, dwell on adversity, are slow to gain confidence after experiencing failure, and easily encounter stress and depression ( Mlatsheni, 2012 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 97%
“…Views of Bandura (1994) underscore this by stating that the higher an individual’s level of perceived self-efficacy, the wider the variety of career paths they seriously consider, the more interest they show in diverse career paths, and they are generally better prepared to deal with success and failures. Moreover, research shows that in relation to academic achievement, individuals with lower levels of self-efficacy achieve lower levels of academic success and continuous failure may lead to learned helplessness ( Juan et al, 2018 ). Learned helplessness is a psychological state where an individual avoids tasks that require persistence, interpret failure as a result of their lack of skills, negatively perceive tasks as challenges, and display a lack commitment ( Filippello et al, 2020 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Factors that influence students' learning attitudes include their teachers, parents, and peers, with the teacher's teaching strategies and learning environment being the most significant [33]. Students translate positive classroom experiences into positive attitudes and learning efforts, thus influencing their ultimate academic performance [34]. Therefore, teachers must create positive classroom experiences for student learning.…”
Section: Learning Attitudesmentioning
confidence: 99%